KONSELOR SEBAGAI PEMIMPIN DI SEKOLAH - tri Nurza Rahmawati; Mudjiran Mudjiran; Neviyarni Neviyarni; Herman Nirwana (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2020)
There has long been concern about advisors in schools because their roles change quickly and significantly in response to trends in society. This has resulted in various conceptions and misconceptions about their roles. This article describes the emergence of school counseling as a profession, outlining the history of the development of the school counseling model (eg vocational guidance, mental health movements, and developmental guidance). Counselors in schools must be promoted as leaders or provide recommendations to school counselors who seek leadership-related status. Furthermore, the authors explain that tactical advocacy for marginalized students and targeted partnerships with school principals are an integral part of strengthening a school counselor. Recommendations are offered for counselors in schools to be able to hone the importance of leadership skills, especially through professional development (for example in services, distance learning and continuing education courses).Keywords: Counseling, School, Leadership